Rub‐Resistant Antibacterial Surface Conversion Layer on Stainless Steel. Issue 11 (24th February 2022) - Huang, Haiyue; Barber, Olivia Willilams; Yu, Zhilong; Park, Hun; Hu, Xiaobing; Chen, Xinqi; Chen, Chun‐Hu; Hartmann, Erica M.; Huang, Jiaxing
Abstract: Stainless steels are widely used in hospitals and public transportation vehicles as one of the most common touch surfaces. Retrofitting stainless steel surfaces with an antimicrobial layer can bring potential public health benefits by reducing the ability of inanimate objects, or fomites, to transmit infections. Here, a facile surface conversion reaction between stainless steel and a solution of KMnO4 and CuSO4 is reported, which leads to a conformal and robust oxyhydroxide layer. Microscopy observations show that the layer is amorphous, continuous, and pinhole‐free with a thickness of only 10–15 nm. The coating adheres strongly to stainless steel and can resist rubbing in simulated friction tests, which is attributed to its intermixing with the substrate without forming a sharp interface. Cu ions incorporated into the surface layer can be released into water droplets deposited on the surface and induce antimicrobial activities against bacteria ( Pseudomonas aeruginosa PA14) after 30 min of contact. Abstract : A facile solution treatment generates a conformal, continuous, rub‐resistant, and ultrathin coating on stainless steel surface (right), which upon hydration releases Cu ions for antimicrobial purposes.